A cartografia na formação do professor de geografia - Sousa, Sandra Maria (2010)
The theme of this study referred to the geography, more specifically, the Cartography and had the singular object of the research training of teachers of Geography and the possible implications of their actions in the processes of teaching and learning Cartography in Basic Education (Elementary Education II and Middle). The problem was centered on the seemingly superficial way of teaching cartography, or perhaps in the low priority given to this subject in the lessons of Geography in Primary Education -. From this perspective, arose the first assumption that the problem would be based, or could be in teacher education that might not work the importance of cartography. By corollary, rose a second proposition: the alleged failure of theoretical and methodological is leading to disinterest in the subject by the teacher of basic education and, consequently, by the student, even as a reflex action. Thus, the goal was to analyze the importance of cartography in initial teacher training university in Geography, for her performance in Basic Education, and as specific objectives to reach the overall goal stood out: analysis of the presence of mapping the National Curriculum Guidelines - DCNs; waiver of the need to invest in training of teachers of geography, research on students of their expertise in cartography, and offering subsidies to the debate about the training of teachers of Geography. The theme was developed from theoretical and empirical research. So, being a literature search of academic procedure inevitable, she sought to bring the state of the art in relation to the subject under investigation. As a tool for data collection were used questionnaires to students in 8th grade of elementary school and 3 years of high school, for teachers of Geography and Basic Education for university teachers of Cartography. As an immediate result, it is stated in this study, reflections on alternatives aimed at strengthening relations between university and school in order to fulfill the role of higher education, namely, to produce and socialize promoting the advancement of knowledge knowledge and know-how